Assessment of wash practices among women in urban slums of Berhampur, Odisha: a cross sectional study - Tripathy, Radha Madhab; Acharya, Geeta Chand; Karmee, Nivedita (International Journal of Research in Medical Sciences, 2017)
Background: Access to Water, Sanitation and Hygiene (WASH) is a pre- condition for people to acquire good health, well-being and benefit from economic development. WASH constitutes both provision of water and sanitation facilities and hygiene promotion. The study objective is to assess the practices and existing perceptions of water, sanitation and hygiene among women in urban slums of Berhampur. Methods: A cross sectional study was conducted among 400 women (households) residing in urban slums of Berhampur from August2016-January 2017 by simple random sampling. Data was collected using a predesigned pretested questionnaire. Results: Out of the total, 62.3% respondents depended on public tap as major source of drinking water , 31.5% purified water before drinking , 68.5% allowed water to stand for a day before use , 86.5% practiced hand wash before meal , 33.2% practiced open defecation, 7% and74% used soap and water for handwashing before meal and after defecation respectively, 68.3% threw liquid wastes haphazardly, 59.8% threw solid wastes haphazardly into drains, 78.5% respondents children had a history of diarrhoea in the past 6 months and 86.8% had flies menace in their houses. Conclusions: Components such as purification of water (31.5%), open defecation (33.2%), hand washing with soap and water before meal (7%), indiscriminate disposal of waste suggest a long way to go to achieve the targets of SDG -6. Adequate IEC activities are needed for effective WASH Strategy implementation.